SIMULASI PERENCANAAN JARINGAN LONG RANGE (LORA) PADA AREA KOTA SEMARANG MENGGUNAKAN CLOUD RF - Susilo, Dhea Ernanda; Jayati, Ari Endang; Muliandhi, Puri (Power Elektronik : Jurnal Orang Elektro, 2023)
LoRa is a wireless technology used to connect devices in a network designed to enable remote communication. LoRa is able to answer the challenges of implementing IoT with the various advantages it offers. However, with the advantages offered, the use of LoRa is still limited for now. So a simulation and feasibility analysis is needed to what extent LoRa can be applied in urban environments. In this study, a simulation analysis of LoRa network coverage in Semarang City was carried out using Cloud RF software. This simulation aims to study the signal quality and coverage of existing LoRa networks in Semarang City. From this simulation will provide a better understanding of the performance of the LoRa network in the city of Semarang. The results of this simulation show that the LoRa network coverage in Semarang City reaches 47.56%, and the unreached areas or blank spots reaches 52.44%. Thus, this evaluation can be used as a basis for optimizing the LoRa network in Semarang City.